7 Radicals and Rational Exponents
7 Radicals and Rational Exponents
7 Radicals and Rational Exponents
Expressions
2021
ii
1
1. an − b = 0 and
Note:
√
• For any integer n ≥ 1, n 0 = 0
√
• n b does not exist if b < 0 and n is even.
Equivalently,
m √
n
√
n
b n = ( b)m = ( bm ).
Definition 0.0.5 Recall that two positive integers m and n are relatively
prime if they have no common divisor greater than 1.
2
2
• (−8) 3
Solution:
2 p
3
(−8) 3 = (−8)2
√
3
= 64
=4
or
2 √
(−8) 3 = ( 3 −8)2
= (−2)2
=4
2
• (8) 3
Solution:
2 p
3
(8) 3 = (8)2
√
3
= 64
=4
or
2 √
(8) 3 = ( 8)2
3
= 22
=4
3
4
• (−8) 6
Solution:
4 2
(−8) 6 = (−8) 3
=4
Note that the rational exponents also satisfy the laws of integral exponents.
Recall:
am
4. 4th Law: If a 6= 0, then an
= am−n if m > n.
am
5. 5th Law: If b 6= 0, then ( ab )m = bm
.
Example 0.0.10 Remove the negative and zero exponents and simplify.
− 3
1
• ( x− 57 )− 4
x 10
4
Solution:
3
x− 5 1 3 7 1
( 7
− 10
)− 4 = (x− 5 x 10 )− 4
x
3 7 1
= (x− 5 + 10 )− 4
1 1
= (x 10 )− 4
1
= x− 40
1
= 1
x 40
1
√
= 40
x
Example 0.0.11 Remove the negative and zero exponents and simplify.
7 4
2 3 −9 1
• ( xx0yy−1zz −2 )− 7
Solution:
7 4
x 2 y 3 z −9 1 7 4 1
( 0 −1 −2 )− 7 = (x 2 y 3 +1 z −9+2 )− 7
xy z
7 7 1
= (x 2 y 3 z −7 )− 7
1 1
= x− 2 y − 3 z 1
z
= 1 1
x2 y 3
Example 0.0.12 Remove the negative and zero exponents and simplify.
1 1 1 1
• (a 4 − a 2 )(a− 4 + a− 2 )
5
Solution:
1 1 1 1 1 1 1 1 1 1 1 1
(a 4 − a 2 )(a− 4 + a− 2 ) = a 4 − 4 − a 2 − 4 + a 4 − 2 − a 2 − 2
1 1
= a0 − a 4 + a− 4 − a0
1 1
= −a 4 + a− 4
1 1
= 1 − a4
a4
1 1
1 − a4+4
= 1
a4
1
1 − a2
= 1
a4
LAWS OF RADICALS
Laws of Radicals
√ 1
1. ( n a)n = (a n )n = a
√ 1 1 1 √ √
2. n ab = (ab) n = a n · b n = n a · n b
1 1 √
na
n a
= ( ab ) n = an
p
3. b 1 = n ,
√
b
provided that b 6= 0
bn
p
m n
√ 1 1 1 1 √ √
4. a = (a n ) m = a nm = a mn = mn a, provided that mn a exists
√ n
5. n an = a n = a, provided that a > 0, or a < 0 and n is odd
√
• ( 3)2
6
Solution:
√
( 3)2 = 3
√
• 3
216
Solution:
√
3
p
3
√
3
√
3
216 = 8(27) = 8 · 27 = (2)(3) = 6
√
• √2
8
Solution:
√ r r
2 2 1 1
√ = = =
8 8 4 2
Solution:
√ 3 √ √
q q
3 3
4= 4= 2
√
• 5
−32
7
Solution:
√
5
p
−32 = 5 (−2)5 = −2
√
• 5
32
Solution:
√
5
√
5
32 = 25 = 2
Simplification of Radicals
√
• 3
16
Solution:
√
3
√
3
√
3
√
3
√
3
16 = 23 · 2 = 23 · 2 = 2 2
√
• 50
Solution:
√ √ √ √
50 = 25 · 2 = 25 · 2
√
=5 2
8
Solution:
r r r √
3
3 5 3 5 32 x 3 45x 45x
= · = =
3x2 3x2 32 x 33 x3 3x
√
• 4
64
Solution:
√
4
q
√ √ √ √
64 = 64 = 8= 22 · 2 = 2 2
Solution:
sr
2√
r r
4 64a2 b2 (23 )a2 b2 23 ab c
= = · = 2abc
c2 c2 c c c
√
• a−2 + b−2
9
Solution:
r r √
p 1 1 b2 + a2 b 2 + a2
a−2 + b−2 = + = =
a2 b2 a2 b2 ab
•
p
4
m−2 − 2m−1 + (2m)0 , where m < 1.
Solution:
r
p 41 2
4
m−2 − 2m−1 + (2m)0 = 2
− +1
r m m
2
4 1 − 2m + m
=
r m2
2
4 (1 − m)
= 2
sr m
(1 − m)2
=
m2
r
1−m
=
r m
1−m m
= ·
r m m
m − m2
= 2
√ m
m − m2
=
m
10
OPERATIONS ON RADICALS
Addition and Subtraction of Radicals
Similar Radicals
Solution:
√
3
√
3
√
3
√
3
16 − 54 = 23 · 2 − 33 · 2
√3
√
3
=2 2−3 2
√3
= (2 − 3) 2
√ 3
=− 2
Solution:
√ √ √ √ √
3 a + b − 5 a + b + 4 a + b = (3 − 5 + 4) a + b = 2 a + b
Solution:
√3
√
3
√ √4
40a4 − 3a 135a − 20a3 + 4a 25a2
√ √ √ √
q
3 3
3 3 3 2 2
= 2 · 5 · a · a − 3a 3 · 5a − 2 · 5 · a · a + 4a 25a2
√3
√
3
√ √
=2a 5a − 9a 5a − 2a 5a + 4a 5a
√3
√
=(2a − 9a) 5a + (4a − 2a) 5a
√ √
3
=2a 5a − 7a 5a
and
√ r
n
a a
√
n
= n
.
b b
12
Solution:
√
3
√
3
√
3
2· 4= 8=2
Solution:
√
3
r r r r √
3
2 2
3 2 3 1 3 2 3 4 4
√ = = · 2
= =
3
4 4 2 2 8 2
Solution:
√ √ √ √ √ √
( 5 + 2 3)( 5 − 2 3) = ( 5)2 − (2 3)2
= 5 − 4(3)
= 5 − 12
= −7
13
Solution:
√ √
√ √ √ 2 6 3 14 √ √
(2 6 + 3 14) ÷ 2 = √ + √ = 2 3 + 3 7
2 2
Solution:
√ √
r
4 4 464a3 b
64a3 b ÷ 4ab3 = 3
r 4ab
2
4 16a
= 2
r b r
2 2
4 16a 4 b
= 2
·
r b b2
2 2
4 16a b
= 4
p√ b
16a2 b2
=
√ b
4ab
=
√b
2 ab
=
b
14
√ √
• 3
5· 3
Solution:
√
3
√ 1 1
5· 3 = 53 · 32
2 3
= 56 · 36
1
= (52 33 ) 6
√6
= 675
√
4
• √12
3
15
Solution:
√
4 1
12 12 4
√ = 1
3 32
1
12 4
= 2
r34
4 12
=
r9
4 4
=
r3
4 4 33
= ·
p 3 33
4
27(4)
= √ 4
√ 34
4
108
=
3
√ √
•
p
2x · 3
3y ÷ 4
4x3 y
16
Solution:
√ p p 1 1 1
2x · 3 3y ÷ 4 4x3 y = (2x) 2 (3y) 3 ÷ (4x3 y) 4
6 4 3
= (2x) 12 (3y) 12 ÷ (4x3 y) 12
p p p
= 12 (2x)6 · 12 (3y)4 ÷ 12 (4x3 y)3
√
12
p p
= 26 x6 · 12 34 y 4 ÷ 12 43 x9 y 3
p
12
26 x6 · 34 y 4
= p 12
26 x9 y 3
s
26 34 x6 y 4
= 12 6 9 3
2xy
r r r
4 4 9
12 3 y 12 3 y 12 x
= 3
= ·
rx p x3 x9
4 9 12
34 x 9 y
12 3 x y
= =
x12 x
Solution:
√ √
3
√
6 1 1 1
ab · a2 ÷ 2 a7 b3 = (ab) 2 · (a2 ) 3 ÷ 2(a7 b3 ) 6
3 2 1
= (ab) 6 · (a2 ) 6 ÷ 2(a7 b3 ) 6
√6
√
6
√6
= a3 b3 · a4 ÷ 2 a7 b3
√ 6
a7 b3
= √ 6
2 a7 b3
1
=
2